Knowledge, attitude and practice towards smoking among International Islamic University Malaysia Kuantan communities - A.H., Nurul 'Izzati; A.Rahman, Nor Azlina; A.Rahman, Nor Iza; Haque, Mainul (International Islamic University Malaysia, 2016)
Smoking is an issue that has spread around the world throughout the years. The majority of smokers have the intention to quit smoking, but due to some factors, it may prevent their intention. Research and interventions have been done in many countries to decrease the smoking prevalence. This cross-sectional study aimed to find out the associations of knowledge, attitude and practice (KAP) towards smoking and to identify the factors associated with knowledge and attitude towards smoking, in priority to sociodemographic factors among the International Islamic University Malaysia Kuantan (IIUMK) communities, including between students and workers. One hundred fifteen respondents of students and workers from IIUMK were investigated with a self-administered questionnaire starting from 10-01-2014 to 10-02-2014. The data were analysed using SPSS software. Respondents had good knowledge and practice, and moderate attitude towards smoking. There was weak positive correlation between knowledge with attitude (r=+0.193, p=0.038) and practice (r=+0.206, p=0.028), also moderate correlation between attitude and practice towards smoking (r=+0.626, p<0.001). There was no factor found to be associated with knowledge, but significant association was found between attitude towards smoking with gender (p<0.001), education level (p=0.016) and smoking status (p<0.001). Although, the mean values of KAP levels were higher for workers, but it was not statistically significant as compared to the students. These study findings suggested that the main obligation are more for students to improve their KAP level towards smoking as they are fresh generation who will educate and lead the upcoming generation of Malaysia.